2020
DOI: 10.1108/ijaim-08-2020-0129
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of e-learning beyond MOOCs for higher education

Abstract: Purpose This paper aims to explore factors influencing university students’ intent to take formal lectures completely through e-learning with cloud meetings. Design/methodology/approach This study has surveyed Chinese students who have experienced e-learning with cloud meetings as well as traditional massive open online courses (MOOC) without live dialogues. The data are analysed based on structural equation modelling to assess factors influencing students’ intent to choose e-learning with cloud meetings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 47 publications
3
18
0
1
Order By: Relevance
“…It is also noteworthy that the teacher's behavior critically mediates the relationship between system usability and learning outcomes, especially in epidemic crises such as COVID-19. This study's results are in line with those of previous studies by Burch et al (2015) and Liu (2021). They concluded that the perceived ease of use induces the perceived usefulness of the electronic learning system and their intention to use the system and high involvement within the educational process.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is also noteworthy that the teacher's behavior critically mediates the relationship between system usability and learning outcomes, especially in epidemic crises such as COVID-19. This study's results are in line with those of previous studies by Burch et al (2015) and Liu (2021). They concluded that the perceived ease of use induces the perceived usefulness of the electronic learning system and their intention to use the system and high involvement within the educational process.…”
Section: Discussionsupporting
confidence: 91%
“…The damage caused by the epidemic crisis constitutes several prevailing challenges that are insufficiently investigated. Limited studies have examined the factors that influence the students' online learning outcomes in the HEIs affected by the forced social distancing during the COVID-19 pandemic period (Lie et al, 2020;Liu, 2021;Mallillin et al, 2020). Recent studies revealed that there is a need to further explore the structural and psychological factors affecting student online learning and engagement (Farrell and Brunton, 2020).…”
Section: Learning Outcomes and Online Engagementmentioning
confidence: 99%
“…Online delivery platforms engage students in active learning (George et al, 2014;Kekkonen-Moneta and Moneta, 2002) and support self-regulated learning (Paechter and Maier, 2010). Prior research on systems characteristics has examined the features of e-learning systems (Davies and Graff, 2005;Liu, 2021). Liu (2021) uses the technology acceptance model to compare an e-learning system (massive open online courses) without virtual meetings to another e-learning system with virtual meetings.…”
Section: Effect Of Game-based Learning On Performancementioning
confidence: 99%
“…Prior research on systems characteristics has examined the features of e-learning systems (Davies and Graff, 2005;Liu, 2021). Liu (2021) uses the technology acceptance model to compare an e-learning system (massive open online courses) without virtual meetings to another e-learning system with virtual meetings. The results reveal that college students in China perceive e-learning with virtual meetings on cloud conference platforms as easier to use and more beneficial, leading to increased usage of an e-learning system with virtual meetings (Liu, 2021).…”
Section: Effect Of Game-based Learning On Performancementioning
confidence: 99%
See 1 more Smart Citation